Characterizing the profile of obese patients who are metabolically healthy - Primeau, V; Coderre, L; Karelis, A.D; Brochu, M; Lavoie, M.E; Messier, V; Sladek, R; Rabasa-Lhoret, R (International Journal of Obesity, 2011)
The presence of obesity-related metabolic disturbances varies widely among obese individuals. Accordingly, a unique subset of obese individuals has been described in the medical literature, which seems to be protected or more resistant to the development of metabolic abnormalities associated with obesity. These individuals, now known as 'metabolically healthy but obese' (MHO), despite having excessive body fatness, display a favorable metabolic profile characterized by high levels of insulin sensitivity, no hypertension as well as a favorable lipid, inflammation, hormonal, liver enzyme and immune profile. However, recent studies have indicated that this healthier metabolic profile may not translate into a lower risk for mortality. Mechanisms that could explain the favorable metabolic profile of MHO individuals are poorly understood. However, preliminary evidence suggests that differences in visceral fat accumulation, birth weight, adipose cell size and gene expression-encoding markers of adipose cell differentiation may favor the development of the MHO phenotype. Despite the uncertainty regarding the exact degree of protection related to the MHO status, identification of underlying factors and mechanisms associated with this phenotype will eventually be invaluable in helping us understand factors that predispose, delay or protect obese individuals from metabolic disturbances. Collectively, a greater understanding of the MHO individual has important implications for therapeutic decision making, the characterization of subjects in research protocols and medical education.